2013
DOI: 10.1177/0273475313481157
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of the Literature for Sales Educators

Abstract: The Journal of Marketing Education is publishing a special issue on Sales Education and Training in August 2014. In this article, we review the sales education literature from four primary journals and the business literature at large. The four primary journals are the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(134 citation statements)
references
References 76 publications
3
122
1
Order By: Relevance
“…There is a shortage in qualified salespeople (Cummins et al, 2013) and a growth in sales postions (U.S. Bureau of Labor Statistics, 2012). The growth in sales curricula (Cummins et al, 2013;Deeter-Schmelz & Kennedy, 2011;Dixon & Tanner, 2012) highlights how educators have responded to meet this need.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a shortage in qualified salespeople (Cummins et al, 2013) and a growth in sales postions (U.S. Bureau of Labor Statistics, 2012). The growth in sales curricula (Cummins et al, 2013;Deeter-Schmelz & Kennedy, 2011;Dixon & Tanner, 2012) highlights how educators have responded to meet this need.…”
Section: Resultsmentioning
confidence: 99%
“…This project can be tweaked to fit different time frames and different formats, thus contributing to a gap in the literature, with recent scholars asking for effective hybrid and online sales pedagogies to be shared (Cummins et al, 2013;Deeter-Schmelz & Kennedy, 2011). For example, an online class could use the B2B portion of this project, with students calling on prospects in their respective areas.…”
Section: Adaptabilitymentioning
confidence: 99%
“…(e.g., Finch, Nadeau, & O'Reilly, 2012;Pefanis Schlee & Harich, 2010). Lastly, some researchers have sought to unravel the knowledge and skill requirements linked to specific jobs such as sales (e.g., Cummins et al, 2013), product or brand management (e.g., Browne, 1979), advertising (e.g., Kerr, Waller, & Patti, 2009), database marketing (Pefanis Schlee & Harich, 2010) and commercial research (e.g., Freeman & Spanjaard, 2012). The present study has applied this precise approach by examining job conditions in business development, a vigorous labor market sector.…”
Section: Discussionmentioning
confidence: 99%
“…This recognition is indicated by the review of literature by Cummins et al (2013). This review used only four common outlet journals for sales education research and found 107 articles.…”
Section: Introductionmentioning
confidence: 99%